2019
DOI: 10.1097/sle.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Melatonin on Sleep Quality After Laparoscopic Cholecystectomy: A Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction:The efficacy of melatonin to improve sleep quality after laparoscopic cholecystectomy remains controversial. We conduct a systematic review and meta-analysis to explore the influence of melatonin intervention versus placebo on sleep quality after laparoscopic cholecystectomy.Methods: We searched PubMed, EMbase, Web of Science, EBSCO, and Cochrane library databases through July 2018 for randomized controlled trials assessing the effect of melatonin intervention versus placebo on sleep quality after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Similar to a recent meta-analysis in cholecystectomy, melatonin interventions showed no substantial impact on sleep quality and pain score after 1 and 3 hours. 31 However, Kirksey A. et al concluded melatonin did not have effect on subjective sleep assessment but improved sleep efficiency and sleep time by actigraphy wrist bracelet measurement. 32 Acute postoperative pain after hysterectomy may be complicated by anxiety state and psychological factors.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to a recent meta-analysis in cholecystectomy, melatonin interventions showed no substantial impact on sleep quality and pain score after 1 and 3 hours. 31 However, Kirksey A. et al concluded melatonin did not have effect on subjective sleep assessment but improved sleep efficiency and sleep time by actigraphy wrist bracelet measurement. 32 Acute postoperative pain after hysterectomy may be complicated by anxiety state and psychological factors.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to a recent meta-analysis in cholecystectomy, melatonin interventions showed no substantial impact on sleep quality and pain score after 1 and 3 hours. [33] However, Kirksey A. et al concluded melatonin did not have effect on subjective sleep assessment but improved sleep e ciency and sleep time by actigraphy wrist bracelet measurement. [34] Acute postoperative pain after hysterectomy may be complicated by anxiety state and psychological factors.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, the duration of melatonin administration ranged from 3 to 3.5 years, or preoperative temporarily. [24,25,29] Diagnostic criteria for reported mental illness also varied, using NINCDS-ADRDA, ICD-10, or DSM-IV. [20,[30][31][32] The most frequently performed subgroup analysis was high versus low dose of melatonin.…”
Section: Study Characteristicsmentioning
confidence: 99%